An Investigation To The Implementation Of The Student Centered Approach (SCA): A Case On English Language Teaching - Pham Thi Quynh Trang; Melvin M. Simanjuntak; Yanti Kristina Sinaga (Genius Journals, 2021)
The traditional teaching technique limits the quality of education; as a result, learners are unable to satisfy society's rapidly increasing needs. Indeed, in today's world of globalization and technology, learners must actively absorb enormous amounts of knowledge and skills in order to keep up with the upward trend of globalization. Also, in today's age of globalism, having a global language is necessary for all countries throughout the world to engage and communicate with one another, and there is no language better suited to this function than English. As a result, it is critical to strengthen EFL learners' abilities to talk with native speakers and access the most upto-date information and technology on a global scale. As a result, teaching and learning techniques, particularly in English, must evolve from being primarily teacher-centered to being more student-centered. As a result, one of the goals of this research is to answer the question of whether this student-centered method is decent, scientific, and global.
Keywords: Education; English; Knowledge and Skills; student